The Realizations and Functions of Figurative Speeches in Novels Written by Prasetyo Utomo - Arifiyanto, Fajar; Nuryatin, Agus; Doyin, Mukh (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2020)
Utomo’s novels are very related to the theme of religion and culture. The language used tends to be simple but still interesting and beautiful so research on the form and function of language style is very interesting. The purpose of this study is to describe the form and function of language style in the three Utomo novels. Data collection is done by heuristic techniques or read by repeatedly. Data analysis method used is hermeneutics. Almost all types of figurative language styles are found, but for the sake of effective exposure, only three data would be presented as examples of the form of language style and the function of language style. The three most found figurative languages are metaphor, simile, hyperbole, personification, and sinekdoke. The function of language also varies, starting from clarifying the picture, increasing the impression, shortening the narrative, and describing the character's feelings. Fulfillment of these functions with simple but beautiful forms of language style makes Utomo's novels have high aesthetic value and are easily understood by readers.